EFFECTIVENESS OF LECTURE METHOD IN INCREASING KNOWLEDGE RELATED TO ADOLESCENT HEALTH - Anggraini, Sevrima; Nauli, Humaira Anggie; Prastia, Tika Noor; Putri, Bella Rahmawati; Aoliyai, Ika Nida’ul; Aisah, Nurul; Ainniah, Yayah Khoerotul (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Adolescence is a transition period towards adulthood. Adolescence is a very important part of Indonesia, which is currently experiencing a demographic bonus. This phase must be utilized optimally by ensuring that the adolescent population as a productive population must be ready in terms of education, skills, character, and health. Adolescent health education is a strategic program aimed at enhancing adolescents understanding of various health-related issues. The purpose of this study was to evaluate the effectiveness of the lecture method in improving adolescents knowledge related to their health. This study used a quantitative analytical method with a quasi-experimental study design with one group pre-test and post-test design. The research sample consisted of 74 male and female students from 2 high schools in Bogor City. The sampling technique used the accidental sampling method. The results of the study showed an increase in student knowledge scores between before and after being given education using the lecture method (p-value = 0.001). The conclusion of this study is that the adolescent education method with lectures is effective in increasing student knowledge related to adolescent health.